Potential Use of Recycled Aggregate As An Alternative For ordinary Aggregate in Concrete - Lee, Yun Gen (2017)
Recycled aggregate is considered as reused substance coming from the previous used construction or demolition of buildings. In order to reduce such waste material and reduce the usage of ordinary aggregate, it is added into to concrete mix. This study focuses mainly on the effect of recycled aggregate in concrete in terms of workability, compressive strength, flexural strength and water absorption. The course aggregate was replaced by recycled aggregate in certain range of weight percentage, then various test were conducted and data obtained was compare to the control sample. From the water absorption test of aggregate, recycled aggregate has a lower initial water content and higher water absorption rate, compared to ordinary aggregate. Results showed that recycled also increased the slump value and workability of concrete. 20% of the recycled used aggregate replacement is the optimum percentage has archived because it yields the highest compressive strength of the concrete, by 15% approximately. Similar to the flexural strength, 20% of recycled aggregate replacement has reached the highest value of flexural strength as well. As for durability performance, due to the cement paste sticking on the surface of recycled aggregate, its high porosity helps the recycled aggregate to absorb more water than regular aggregate. The study suggests that recycled aggregate is beneficial to the concrete in aspect of workability and mechanical performance, thus it should be cast into concrete mixing, to reduce the water of unused material. Moreover, it would help in preserving the environment.